1978
DOI: 10.1136/jcp.31.11.1073
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of immunoperoxidase and immunofluorescence staining for detecting chlamydia in conjunctival scrapings and in cell culture.

Abstract: (Kurstak et al., 1975), and to study the development cycle of Chlamydia psittaci in peritoneal macrophages of infected mice (Mields et al., 1974

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Direct detection of cytoplasmic inclusions was achieved by a variety of stains (Giemsa, Castañ eda, Machiavello, Stamp, Giménez). The introduction of the immunofluorescence (Woodland et al, 1978) using polyclonal or monoclonal antibodies against the major outer membrane protein (MOMP), which is conjugated with fluorescein isothiocyanide, has been an additional step to further improve specificity and sensitivity of cell culture assays (Langhammer, 1989;Eidebenz, 1991;Fischer, 1992;Dove, 1995;Unkrig, 1995;Andersen et al, 1997;Andersen, 2000).…”
Section: Aetiologic Aspects Of Chlamydiamentioning
confidence: 99%
“…Direct detection of cytoplasmic inclusions was achieved by a variety of stains (Giemsa, Castañ eda, Machiavello, Stamp, Giménez). The introduction of the immunofluorescence (Woodland et al, 1978) using polyclonal or monoclonal antibodies against the major outer membrane protein (MOMP), which is conjugated with fluorescein isothiocyanide, has been an additional step to further improve specificity and sensitivity of cell culture assays (Langhammer, 1989;Eidebenz, 1991;Fischer, 1992;Dove, 1995;Unkrig, 1995;Andersen et al, 1997;Andersen, 2000).…”
Section: Aetiologic Aspects Of Chlamydiamentioning
confidence: 99%
“…They reported that IF staining had been shown to be sufficiently more sensitive and rapid than Giemsa or iodine staining in the detection of C. trachomatis inclusions. On the other hand, earlier reports have also shown that IF staining is more sensitive and specific for the direct detection of C. psittaci inclusions in the clinical specimens (Woodland et al 1978 ;Hanna et al 1965). However, it has been difficult to detect inclusions in conjunctival scrapings from newborns.…”
Section: Discussionmentioning
confidence: 89%
“…Giemsa staining has been found to be slightly less sensitive than the immunocytochemical methods but is more convenient for clinic use. Moreover, problems of artifact are minimal with the Giemsa method (Woodland et al, 1978). Inoculation of monolayer cultures of irradiated McCoy cells with conjunctival swabbings provides another method of detecting C. trachomatis, but facilities for this investigation are available in only a few specialist laboratories, thereby emphasing the value of cytology in routine clinical practice.…”
Section: Diagnosis Of Oculoviral Infectionmentioning
confidence: 99%